Development of Practicum Tools for Learning the Concept of Light Interference Assisted by the ESP-32 Camera Sensor to Practice Science Process Skills - Putri, Dita Shanda; Herlina, Kartini; Anggreini, Anggreini (Universitas Muhammadiyah Purworejo, 2024)
This research aims to develop a practicum tools with assisted by the ESP-32 camera sensor which can be used in learning the matter of light interference at school, as well as to train science process skills. This research uses a Design and Development Research (DDR) approach, which is divided into three stages, that are analysis, design and development, and eval_uation. Before this practicum tool is used in the field to help the learning process, this practicum tool is tested for feasibility first. The feasibility test of the practicum tools for the matter of light interference was carried out using a validity test and practicality test. The results of the practicum tools validity test obtained a percentage of 86% with a very valid category and the indicator for the usefulness of practicum tools in science process skills was 81%. The results of the practicality test obtained a percentage of 84% in the very practicality category. Based on these two feasibility tests, it can be concluded that the practicum tool is suitable for use in learning the matter of light interference at school, and can train students' science process skills. Indicators of scientific process skills that are trained are observing, communicating, controlling variables, hypothesizing, experimentation, and interpreting data.